2019
DOI: 10.1177/0844562119828905
|View full text |Cite
|
Sign up to set email alerts
|

Resettled Bhutanese Refugees in Ottawa: What Coping Strategies Promote Psychological Well-Being?

Abstract: Background Since 2008, Bhutanese refugees have been resettled in Canada, including Ottawa. This relocation and resettling process is associated with significant physical and psychological stress, as individuals acclimatize to a new country. Purpose To assess the relationship between coping strategies and psychological well-being of Bhutanese refugees resettled in Ottawa. Methods A cross-sectional survey utilizing a convenience sample of adults (n = 110) was conducted in the fall of 2015 in Ottawa. Two tools, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…PD is common among Bhutanese refugees in the United States, Canada, and Australia (Adhikari et al, 2015; Ao et al, 2016; Kim et al, 2017; Subedi, 2016; Vonnahme et al, 2015). PD can present with symptoms of anxiety and depression including physical and psychological symptoms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…PD is common among Bhutanese refugees in the United States, Canada, and Australia (Adhikari et al, 2015; Ao et al, 2016; Kim et al, 2017; Subedi, 2016; Vonnahme et al, 2015). PD can present with symptoms of anxiety and depression including physical and psychological symptoms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most of the studies were conducted in high income countries such as Australia [ 43 , 53 , 71 , 78 , 88 , 107 , 116 , 118 ], Canada [ 63 , 64 , 87 , 100 ], and the USA [ 35 37 , 39 , 40 , 42 , 47 , 50 , 52 , 58 , 70 , 76 , 81 , 89 , 98 , 106 , 109 , 110 , 112 ], with fewer being conducted in low and middle income countries: in Congo [ 99 ], Chile [ 79 ], Ghana [ 119 ], India [ 62 ], Jordan [ 38 , 90 , 95 ], Kenya [ 55 , 104 ], South - Korea [ 66 , 80 , 120 ], Nepal [ 121 ], South Africa [ 96 ], Thailand [ 68 ], South-Africa [ 96 ] and Turkey [ 45 , 48 , 51 , 54 , 94 ]. Three studies reported that their participants were living in refugee camps [ 65 , 69 , 119 ], while the participants of the remaining studies were living in the community.…”
Section: Resultsmentioning
confidence: 99%
“…Some refugee groups seem to be particularly vulnerable, and Bhutanese refugees in several countries have displayed particular vulnerability (Ferguson, 2011; Shrestha, 2011). A Canadian study involving 110 Bhutanese refugees found that they were at risk of developing psychological distress at any age due to their premigration experiences (Subedi et al, 2019). In Australia, high rates of anxiety, moderate levels of depression and moderate to high levels of acculturative stress were observed in one Bhutanese refugee community (Lumley et al, 2018).…”
Section: Discussionmentioning
confidence: 99%